Consumer Behavior in Plastic Waste Management: Interventions and the Role of Upcycling - Zhang, Boran; Anwar, Rusmadiah Bin; Razak, Mohamed Razeef Bin Abdul (Journal of Posthumanism, 2025)
Plastic pollution has become one of the most urgent environmental and public health crises of the twenty first century (Jambeck et al., 2015; Geyer, Jambeck, & Law, 2017). This paper presents an original research contribution by combining a systematic literature review with posthumanism theory to interrogate Chinese consumer behavior in plastic waste management. We integrate the Theory of Planned Behavior (TPB) and Value–Belief–Norm (VBN) models with a posthumanism lens to propose the Distributed Agency Circular Model (DACM), which reconceives plastic waste as an active participant in socio ecological assemblages. We then deepen the analysis by introducing concepts of material memory and material semiotics to show how upcycling interventions can harness the latent agency of plastic objects. A new Empirical Research Design section outlines a mixed methods approach to empirically validate the DACM through surveys and interviews. Finally, a Cross Cultural Reflection contrasts Chinese policy with practices in the Netherlands, Japan, and Sweden, demonstrating how material agency is variably enacted across contexts. This manuscript meets Journal of Posthumanism’s Original Research criteria by offering novel theoretical insights, rigorous methodological proposals, and practical implications for circular economic strategies.